Predicting immunotherapy outcomes in patients with MSI tumors using NLR and CT global tumor volume - Belkouchi, Younes; Nebot-Bral, Laetitia; Lawrance, Littisha; Kind, Michele; David, Clémence; Ammari, Samy; Cournède, Paul-Henry; Talbot, Hugues; Vuagnat, Perrine; Smolenschi, Cristina; Kannouche, Patricia L.; Chaput, Nathalie; et al. (Frontiers in Oncology, 2022)
Background: Anti-PD-(L)1 treatment is indicated for patients with mismatch repair-deficient (MMRD) tumors, regardless of tumor origin. However, the response rate is highly heterogeneous across MMRD tumors. The objective of the study is to find a score that predicts anti-PD-(L)1 response in patients with MMRD tumors. Methods: Sixty-one patients with various origin of MMRD tumors and treated with anti-PD-(L)1 were retrospectively included in this study. An expert radiologist annotated all tumors present at the baseline and first evaluation CT-scans for all the patients by circumscribing them on their largest axial axis (single slice), allowing us to compute an approximation of their tumor volume. In total, 2120 lesions were annotated, which led to the computation of the total tumor volume for each patient. The RECIST sum of target lesions’ diameters and neutrophile-to-lymphocyte (NLR) were also reported at both examinations. These parameters were determined at baseline and first evaluation and the variation between the first evaluation and baseline was calculated, to determine a comprehensive score for overall survival (OS) and progression-free survival (PFS). Results: Total tumor volume at baseline was found to be significantly correlated to the OS (p-value: 0.005) and to the PFS (p-value: <0.001). The variation of the RECIST sum of target lesions’ diameters, total tumor volume and NLR were found to be significantly associated to the OS (p-values: <0.001, 0.006, <0.001 respectively) and to the PFS (<0.001, <0.001, 0.007 respectively). The concordance score combining total tumor volume and NLR variation was better at stratifying patients compared to the tumor volume or NLR taken individually according to the OS (pairwise log-rank test p-values: 0.033, <0.001, 0.002) and PFS (pairwise log-rank test p-values: 0.041, <0.001, 0.003). Conclusion: Total tumor volume appears to be a prognostic biomarker of anti-PD-(L)1 response to immunotherapy in metastatic patients with MMRD tumors. Combining tumor volume and NLR with a simple concordance score stratifies patients well according to their survival and offers a good predictive measure of response to immunotherapy.